RELATIONSHIP OF SERVICE RECOVERY TOWARDS PATIENT SATISFACTION IN HOSPITAL IN WEST SUMATERA - Rima Semiarty; Rizanda Machmud; Abdiana; Annisa Wahyuni; Prima Kurniati Hamzah (Jurnal Administrasi Kesehatan Indonesia)
Background: Patient satisfaction in the M. Djamil Hospital was recorded as 79.61% between January and March 2018. It signifies that patient satisfaction rate has not met the target set of 85%.